Ranking engineering characteristics in Quality Function Deployment by factoring-in the roof values. (14th January 2008) - Sharma, J.R.; Rawani, A.M.
Quality Function Deployment QFD is a methodology used to achieve higher customer satisfaction. Deriving the Priority Score of ECs from various input variables is the most critical phase in QFD application. Correlations among ECs are always mentioned and are depicted as Roof of the House in Final QFD Matrix, usually in the form of symbols. But, these correlations are seldom factored-in the calculations of ECs Final Priority Scores (FPSs). In this paper an attempt has been made to address the issue by considering the impact of these correlations on the overall calculations. A method is proposed in this paper using weighted average method for the roof value operator in order to prioritise ECs in QFD. The New factored-in Priority Score of an EC is a linear combination of its correlation with other ECs weighted by the ECs Initial Priority Score. An example is cited to demonstrate the application of the proposed approach.